A Review of Environmental, Social and Governance Frameworks in Sustainable Disposal of Waste from Renewable Energy Resources - John Adebisi; Ojetunde Olasunbo; Iheanacho Henry Denwigwe; Prince Anthony Nwachukwu (Journal of Digital Food, Energy & Water Systems)
The shift to renewable energy sources is essential for mitigating climate change, but it also poses fresh challenges for environmentally responsible waste management. This article reviews and investigates the complex problems associated with the disposal of renewable energy components from an environmental, social, and governance (ESG) perspective. The article further highlights the need for thorough oversight and careful management of various components due to the environmental concerns associated with their disposal as they frequently contain hazardous elements. The social effects on communities impacted by disposal procedures are also explored, and the importance of fair distribution of benefits is emphasized. Transparency, accountability, and stakeholder involvement are bolstered by effective governance, a central theme of this discussion that draws on ESG concepts. Successful ESG-integrated disposal plans are demonstrated by industry case studies. Possible hindrances in sustainable disposal are also highlighted with firm suggestions on way-forward, which include; technical innovation and global collaboration. The study underlines the irreplaceable role played by ESG in guiding responsible waste management toward a sustainable, green energy future.